Diagnosis of foot-and mouth disease by real time reverse transcription polymerase chain reaction under field conditions in Brazil - Clarke Neville P; Martin Barbara M; Beckham Tammy R; Silva René R; Serra Claudia V; Barbosa Meirivan S; Reis Jorge R; Paiva Naimes O; Neta Alcina; Paixão Tatiane A; Adams L Garry; Santos Renato L (BMC Veterinary Research, 2008)
Abstract Background Foot-and-mouth disease (FMD) is an economically important and highly contagious viral disease that affects cloven-hoofed domestic and wild animals. Virus isolation and enzyme-linked immunosorbent assay (ELISA) are the gold standard tests for diagnosis of FMD. As these methods are time consuming, assays based on viral nucleic acid amplification have been developed. Results A previously described real-time reverse transcriptase polymerase chain reaction (RT-PCR) assay with high sensitivity and specificity under laboratorial and experimental conditions was used in the current study. To verify the applicability of this assay under field conditions in Brazil, 460 oral swabs from cattle were collected in areas free of FMD (n = 200) and from areas with outbreaks of FMD (n = 260). Three samples from areas with outbreaks of FMD were positive by real-time RT-PCR, and 2 of those samples were positive by virus isolation and ELISA. Four other samples were considered inconclusive by real-time RT-PCR (threshold cycle [Ct] > 40); whereas all 200 samples from an area free of FMD were real-time RT-PCR negative. Conclusion real-time RT-PCR is a powerful technique for reliable detection of FMDV in a fraction of the time required for virus isolation and ELISA. However, it is noteworthy that lack of infrastructure in certain areas with high risk of FMD may be a limiting factor for using real-time RT-PCR as a routine diagnostic tool.